Efficacy and safety of a morning injection of insulin glargine 300 units/mL versus insulin glargine 100 units/mL in adult patients with type 1 diabetes: A multicentre, randomized controlled trial using continuous glucose monitoring. Issue 8 (9th May 2019) - Pettus, Jeremy; Gill, Jasvinder; Paranjape, Sachin; Stewart, John; Malla, Shilpy; Edelman, Steven; Bergenstal, Richard M.; Bode, Bruce
Abstract: Video abstract: View a video abstract for this article. Aims: This multicentre ( N = 104), randomized controlled phase 4 study compared the efficacy and safety of insulin glargine 300 units/mL (Gla‐300) with insulin glargine 100 units/mL (Gla‐100) in patients with type 1 diabetes (T1D). Materials and methods: Patients were randomized 1:1 to self‐perform morning Gla‐300 or Gla‐100 injections daily for 16 weeks. The primary endpoint was percentage of time blood glucose remained in the target range (70–180 mg/dL) during Week 15/16, measured by blinded continuous glucose monitoring. Secondary endpoints included incidence and rate of nocturnal symptomatic hypoglycaemia (≤70 mg/dL), glycaemic variability parameters and safety assessments. Exploratory analyses were performed in patients with glycated haemoglobin (HbA1c) <7.5% at Week 16. Results: Overall, 638 patients with T1D were included (Gla‐300, n = 320; Gla‐100, n = 318). In the modified intent‐to‐treat (mITT) population, no differences between Gla‐300 and Gla‐100 were observed in time in range, in glycaemic variability, or in incidence or rates of nocturnal symptomatic hypoglycaemia. In exploratory analyses of patients with HbA1c <7.5% at Week 16, Gla‐300 recipients had greater improvement in time in range over 24 hours, during the day and at night compared with Gla‐100 recipients ( P < 0.05), with small increases in overall hypoglycaemia. Conclusions: Time in range and glycaemic variability were similar for Gla‐300 and Gla‐100 recipients at the end of study in the mITT population of relatively well‐controlled patients with T1D. In patients with end‐of‐study HbA1c <7.5%, exploratory analyses suggested that Gla‐300 provided improvements in time in range compared with Gla‐100.